The role of Gene Mutations (gyrA, parC) in Resistance to Ciprofloxacin in Clinical Isolates of Pseudomonas Aeruginosa - Zoheir Heshmatipour; Nasibeh Arabameri; Shima Eftekhar Ardebili; Zeinab Jafari Bidhendi (Iranian Society of Pathology, 2021)
Background & Objective: Pseudomonas aeruginosa is an opportunistic pathogen and one of the most common causes of nosocomial infections. This bacterium's antibiotic resistance to the common fluoroquinolone antibiotics, especially ciprofloxacin, is due to mutations in the gyrA and parC genes. This study aimed to investigate the effect of the mutation in (gyrA, parC) on ciprofloxacin resistance in clinical isolates of Pseudomonas aeruginosa.Methods: A total of 140 clinical samples were collected from hospitals. The samples were identified by standard biochemical tests, and the antibiotic resistance was investigated by the disk diffusion method. DNA was extracted from 30 isolates, and PCR was performed. PCR-sequencing was carried out to assess gyrA and parC mutations in drug-resistant isolates. NCBI-Blast and MEGA7 software was used to analyze the nucleotide sequences.Results: 30 clinical isolates were 80% resistant to ciprofloxacin; meanwhile, in 21 samples, mutations were observed. 87/5% of mutations were related to gyrA (Thr83 → Ile), 79/16 % parC (Ser87 → Leu), and 4/18% (Glu91 → Lys). The antibiotic resistance to ciprofloxacin and mutations in gyrA and parC genes in resistant isolates are significantly related to each other (P<0.05). Conclusion: The mutations in the gyrA and parC genes play an essential role in resistance to ciprofloxacin in clinical isolates of Pseudomonas aeruginosa.